Experience and Discussion on Introducing the “Internet Plus” Classroom Into Teaching Physiological Experimentation - Guo, Yan-hong; Chen, Jian; Xin, Min; Wang, Yong; Tan, Jie; Tian, Jing; Liao, Wei-yong; Zhang, Xiao-ling; Su, Min; Pang, Yong-jun; Huang, Wen-jun (Frontiers in Education, 2022)
The “Internet Plus” education model, enabled by the internet, is a type of “Distance learning” education models. To explore the application of “Internet Plus” education in teaching physiological experimentation at Guilin Medical University, undergraduate clinical medicine students from the 2011 to 2013 classes were used as the historical control group for teaching an experimentation class using the traditional teaching model: “teacher-teaching + student-operation.” Undergraduate clinical medicine students from the 2014 to 2018 classes were used as the teaching reform group and were taught using an “Internet Plus” educational model: “microlectures-previewing + test + feedback + student-operation.” The experimentation operating examination results for the two groups of students were analyzed, questionnaire surveys were administered to students in the experimental group and the relevant teachers, and the survey results were counted. The experimentation operating examination results were significantly higher for the students in the teaching reform group (89.3 points) than for the control group students (84.4 points). The excellent rate was higher (69.8% for the reform group and 54.5% for the control group), whereas the failure rate was lower (1.9% for the teaching reform group and 4.3% for the control group). Additionally,90.1% of the students identified with this reform method, and more than 90% believed that the method improved their interest and confidence in surgical operations during pharmacological and pathophysiological experimentation classes in subsequent courses. All teachers in the physiological experimentation course identified with this teaching method, and 81.8% of the teachers of relevant disciplines in a later stage believed that this learning method was more conducive than traditional teaching to cultivating student interest in learning, proactivity, and other factors. Application of an “Internet Plus” educational model for physiological experimentation teaching can help cultivate hands-on operating abilities and improve the learning interest of students.